NEW APPLICATIONS OF PLATELET-RICH PLASMA IN GYNECOLOGY - Anđelić, Mirjana (Srpski medicinski časopis Lekarske komore, 2025)
Letter to the Editor on the Topic of New Applications of Platelet-Rich Plasma (PRP) in Gynecology and Obstetrics – Intrauterine Infusions and Intraovarian Injections.
Keywords: PRP; fertility; OB-GYN; POI; endometrium